Unravelling the drastic range retraction of an emblematic songbird of North Africa: potential threats to Afro-Palearctic migratory birds - Rassim Khelifa (Nature Portfolio, 2017)
Abstract Understanding how culture may influence biodiversity is fundamental to ensure effective conservation, especially when the practice is local but the implications are global. Despite that, little effort has been devoted to documenting cases of culturally-related biodiversity loss. Here, we investigate the cultural domestication of the European goldfinch (Carduelis carduelis) in western Maghreb (Morocco, Algeria and Tunisia) and the effects of long-term poaching of wild populations (1990–2016) on range distribution, socio-economic value, international trading and potential collateral damage on Afro-Palearctic migratory birds. On average, we found that the European goldfinch lost 56.7% of its distribution range in the region which led to the increase of its economic value and establishment of international trading network in western Maghreb. One goldfinch is currently worth nearly a third of the average monthly income in the region. There has been a major change in poaching method around 2010, where poachers started to use mist nets to capture the species. Nearly a third of the 16 bird species captured as by-catch of the European goldfinch poaching are migratory, of which one became regularly sold as cage-bird. These results suggest that Afro-Palearctic migratory birds could be under serious by-catch threat.